UBUNTU IN A POST-APARTHEID SOUTH AFRICAN CONTEXT (The Pretoria Student Law Review, 2021)
In this article, I attempt to determine the position and value of ubuntu in the law of post-apartheid South Africa as well as to determine how ubuntu compares to humanitarianism. To achieve this goal, I examine both ubuntu and humanitarianism but I go further than merely an examination of the two concepts in isolation; a determination of the similarities and differences also takes place. The terms to be used in this study will be ‘traditional ubuntu’, which refers to ubuntu as known and understood by the indigenous people of South Africa, and humanitarianism, as known in the Western civilization.
Keywords: ubuntu; post-apartheid South Africa; humanitarianism; similarities and differences; ‘traditional ubuntu’; Western civilization; indigenous people of South Africa